Character Development of The Main Character in The Film “Elizabeth: The Golden Age.” a Feminist Existential Approach - Lubna Nur Hanifah, Zaqiyah; Fitriyah, Fitriyah (Universitas Cokroaminoto Palopo, 2026)
This study analyses the character development of the main character, Queen Elizabeth I, in the film Elizabeth: The Golden Age (2007) using a Feminist Existential approach. The study aims to examine how Elizabeth’s character evolves as a woman and a ruler amid political pressure, gender constraints, and personal sacrifice within a patriarchal society. Feminist existentialism, particularly drawing on the ideas of Simone de Beauvoir, is employed to explore themes of freedom, choice, responsibility, and self-definition as reflected in Elizabeth’s actions and decisions. This research adopts a qualitative descriptive method, with the film serving as the primary data source. Data are collected through close observation of dialogues, scenes, character interactions, and cinematic elements that reveal Elizabeth’s psychological and ideological development. The analysis focuses on how Elizabeth negotiates her identity between her role as a woman and her position as a monarch, and how she asserts her autonomy despite societal expectations. The findings indicated that the character development of Elizabeth's are; 1) possessing a highly protective spirit, 2) becoming an Intellectual, 3) have self-confidence, 4) responsible, 5) possesses courage, and 6) caring for fellow women. This study contributes to feminist film studies by highlighting the representation of female agency and existential freedom in historical cinema, and it offers insight into how film narratives can reflect women’s struggles for self-determination and leadership.